Тhe superradiance of a bunch of rotating electrons - Kuklin, V.M.; Litvinov, D.N.; Sporov, A.E. (Вопросы атомной науки и техники, 2018)
Equations describing the excitation of a TE wave by a beam of electrons rotating in an external magnetic field in
a waveguide in two regimes were considered. In the first regime the interaction of the oscillators − rotating electrons
in the magnetic field − was neglected. It was assumed that the beam electrons interact only with the waveguide
modes. In the second case, in the superradiance regime, the beam electrons interact with each other due to their
spontaneous radiation. In the article the basic features of the description of the gyrotron gain regime are discussed. Розглянуто рівняння, що описують збудження пучком електронів, що обертаються в зовнішньому магнітному полі ТЕ-хвилі у хвилеводі в двох режимах. У першому режимі нехтуємо взаємодією випромінювачів
– електронів, що обертаються в магнітному полі. Вважаємо, що електрони пучка взаємодіють лише з хвилеводними модами. У другому випадку, у режимі надвипромінювання, електрони пучка взаємодіють один з
одним за рахунок їх спонтанного випромінювання. Обговорюються особливості опису режиму підсилення
гіротрона. Рассмотрены уравнения, описывающие возбуждение пучком вращающихся во внешнем магнитном поле
электронов ТЕ-волны в волноводе в двух режимах. В первом режиме взаимодействием излучателей – вращающихся в магнитном поле электронов, пренебрегаем. Полагаем, что электроны пучка взаимодействуют
только с волноводными модами. Во втором случае, в режиме сверхизлучения, электроны пучка взаимодействуют друг с другом за счет их спонтанного излучения. Обсуждаются особенности описания режима усиления гиротрона.